Proses Pembelajaran Tari Kelinci pada Anak Down Syndrome di SLB Negeri Semarang - Tiara Ayu Sumarlinda; Eny Kusumastuti (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The study aims to describe the process of learning the rabbit dance for children with Down Syndrome at SLB Negeri Semarang. This study uses a qualitative method and a phenomenological approach to describe the teaching and learning atmosphere in the classroom. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the rabbit dance learning process carried out through the planning, implementation, and evaluation stages with demonstration, imitation, and drill methods is believed to be good, because the methods, materials, and approaches applied by the teacher are appropriate,so that children with Down Syndrome can receive the material well but still experience many obstacles. The main obstacles are the weak motor skills of children and low levels of focus during the practice process. Each meeting always experienxes improvements Rabbit dance learning in cognitive, affective, and psychomotor aspects. Suggestions given by researchers are for dance teachers to improve the quality of the teaching and learning process and provide more motivation to students in dance lessons